The development of interactive learning media for biology based on telegram bots on digestive system materials in class VIII Junior High School to train students' critical thinking skills - Ella Zuliana Safitri; Danang Biyatmoko; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The industrial revolution era of 4.0 requires every graduate to have thinking skills, but in reality, these skills are still low in schools. Interactive media is an alternative solution that can be used to train students' critical thinking skills. This study develops a telegram bot to train the students' critical thinking skills on the material of the digestive system. The research method uses the modified Borg & Gall model and is limited to five steps, namely: 1) preliminary research; 2) develop the initial product; 3) expert validation and revision; 4) small field trials and revisions; e) large-scale field trials and final products. The research instruments used were validation questionnaires, response questionnaires, media implementation and learning achievement tests which were then analyzed descriptively. The results show that the telegram bot is very valid with very good legibility. The practicality of the telegram bot is shown by the implementation of the media, with a score of 94.3 and student responses of 93.93. The results of increasing the student's critical thinking skills show an N-Gain of 0.65, categorized as moderate. Therefore, the telegram bot on the digestive system effectively trains students' critical thinking skills.Abstrak Era revolusi industri 4.0 mengharuskan setiap lulusan memiliki keterampilan berpikir, namun realitanya keterampilan ini masih rendah di sekolah. Media interaktif menjadi salah satu solusi alternatif yang dapat digunakan untuk melatihkan keterampilan berpikir kritis siswa. Penelitian ini mengembangkan bot telegram untuk melatihkan keterampilan berpikir kritis siswa pada materi sistem pencernaan. Metode penelitian menggunakan model Borg & Gall yang telah dimodifikasi dan dibatasi hingga lima langkah yakni: 1) penelitian pendahuluan; 2) mengembangkan produk awal; 3) validasi ahli dan revisi; 4) uji coba lapangan kecil dan revisi; e) uji coba lapangan skala besar dan produk akhir. Instrumen penelitian yang digunakan berupa angket validasi, angket respon siswa, keterlaksanaan media dan tes hasil belajar yang dianalisa secara deskriptif. Hasil penelitian menunjukkan bot telegram tergolong sangat valid dengan keterbacaan sangat baik. Kepraktisan ditunjukkan dari keterlaksanaan media dengan skor 94,3 dan respon siswa sebesar 93,93. Hasil peningkatan keterampilan berpikir kritis siswa menunjukkan N-Gain sebesar 0.65 yang terkategori sedang. Oleh karena itu bot telegram materi sistem pencernaan efektif digunakan untuk melatihkan keterampilan berpikir kritis siswa.